Peran Guru Pendidikan Agama Kristen Terhadap Pengaruh Gadget Bagi Perkembangan Moral Peserta Didik - Rejeki Deskristinawati Hia; Yane Henderina Keluanan (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
In the increasingly advanced digital era, gadgets can have a positive impact on students. However, the use of gadgets can also have a negative impact on their understanding and poor practice, therefore PAK teachers need to play a role in overcoming the irresponsible use of gadgets. PAK teachers have a key role in teaching responsible gadget use. They should have a role to play in building awareness of the negative effects of using gadgets; and encourage critical discussion and moral reflection related to gadget use. In addition, Christian religious education teachers strengthen moral education and Christian religious values in learning. They provide creative alternatives that don't rely on gadgets, so students can experience experiences that support their moral development. Collaboration with parents and the church community is also an important part of ensuring messages that are consistent and in line with Christian religious values. By implementing this strategy, PAK teachers can have a proactive role in shaping the moral development of students. With a deep understanding of the influence of gadgets and Christian religious values, students can develop moral attitudes and behaviors that are in accordance with the teachings of Christianity.